The Press as a documental source for social analysis and research. (2019)
The purpose of this article is to analyse the importance of the press as a documental source for the study of political and cultural history based on experiences of historiographic research into the 20th century in Colombia. First, there is an attempt to unveil the meaning and reach of the liberal and conservative press in the 30s and 40s. Then, an attempt is made to show the treatment the press made regarding student demonstrations in the 60s and 70s of the 20th century. Both contrasts will allow the recognition of the evolution and uses of the press as a mediator of public opinion and documental heritage for analysis and social investigation, especially for the study of local and national history. For this reason, there are references to the study of the press through frame analysis, which allows understanding and accounting for  the conscious strategic efforts carried out by certain groups of people in order to construct shared interpretations of the world that motivate collective action.